Comparison of the bactericidal activities of ofloxacin and ciprofloxacin alone and in combination with ceftazidime and piperacillin against clinical strains of Pseudomonas aeruginosa. - Klepser, M E (1995)
On the basis of MIC data, ciprofloxacin exhibits superior activity against Pseudomonas aeruginosa than the other currently available fluoroquinolones do. Despite the antipseudomonal advantage noted for ciprofloxacin monotherapy, it is unknown whether this advantage is maintained when the fluoroquinolones are used in combination with antipseudomonal beta-lactams such as ceftazidime and piperacillin. Twelve healthy volunteers were enrolled in this open-label, randomized, steady-state, six-way cross-over, comparative trial. All subjects received the following regimens: (i) 400 mg of ofloxacin given intravenously (i.v.) every 12 h (q12h), (ii) 400 mg of ciprofloxacin given i.v. q12h, (iii) 400 mg of ofloxacin given i.v. q12h plus 1 g of ceftazidime given i.v. every 8 h (q8h), (iv) 400 mg of ciprofloxacin given i.v. q12h plus 1 g of ceftazidime given i.v. q8h, (v) 400 mg of ofloxacin given i.v. q12h plus 4 g of piperacillin given i.v. q8h, and (vi) 400 mg of ciprofloxacin given i.v. q12h plus 4 g of piperacillin given i.v. q8h. Serum bactericidal titers with subsequent calculation of the area under the bactericidal curve were determined against three clinical isolates of P. aeruginosa. As monotherapy, ciprofloxacin demonstrated superior antipseudomonal activity than ofloxacin did; however, combination of these agents with ceftazidime yielded remarkably similar and statistically comparable activity profiles. In contrast, ciprofloxacin-piperacillin retained a bactericidal advantage over ofloxacin-piperacillin. Although ciprofloxacin exhibits superior antipseudomonal activity when used as monotherapy, combination of ofloxacin or ciprofloxacin with ceftazidime yielded equivalent activity profiles against susceptible strains of P. aeruginosa.